Please answer this question. I will mark you as Brainliest.
Attachments:
![](https://hi-static.z-dn.net/files/dd9/e33dfb6e329c99ae910dc41beb9eeb1a.jpeg)
Answers
Answered by
1
On equating the power
We get the equation as
-3 + 11 = 3x+2
=>8=3x+2
=>8-2 = 3 x
=>3x = 6
=>x = 2
We get the equation as
-3 + 11 = 3x+2
=>8=3x+2
=>8-2 = 3 x
=>3x = 6
=>x = 2
Answered by
1
Answer:
2
Step-by-step explanation:
bases are common hence power will be added for all as they are in multiplication:
(-2/5)^(-3+11)=(-2/5)^(3x+2)
bases are same hence L.HS power = R.H.S power
3x+2=8
x=2
Similar questions